2018
DOI: 10.1136/bmj.k585
|View full text |Cite
|
Sign up to set email alerts
|

Living network meta-analysis compared with pairwise meta-analysis in comparative effectiveness research: empirical study

Abstract: ObjectiveTo examine whether the continuous updating of networks of prospectively planned randomised controlled trials (RCTs) (“living” network meta-analysis) provides strong evidence against the null hypothesis in comparative effectiveness of medical interventions earlier than the updating of conventional, pairwise meta-analysis.DesignEmpirical study of the accumulating evidence about the comparative effectiveness of clinical interventions.Data sourcesDatabase of network meta-analyses of RCTs identified throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 63 publications
1
71
0
4
Order By: Relevance
“…A recent study concluded that living network meta-analyses with continuous updating produce strong, timely evidence of comparative effectiveness 37. The research questions in this systematic review are in line with proposed criteria for continuing a living systematic review, namely: (1) the systematic review is a priority for decision making; (2) new information will change decision making; and (3) there is likely to be, on an ongoing basis, new research relevant to decision making 38 39.…”
Section: Methods and Analysismentioning
confidence: 99%
“…A recent study concluded that living network meta-analyses with continuous updating produce strong, timely evidence of comparative effectiveness 37. The research questions in this systematic review are in line with proposed criteria for continuing a living systematic review, namely: (1) the systematic review is a priority for decision making; (2) new information will change decision making; and (3) there is likely to be, on an ongoing basis, new research relevant to decision making 38 39.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Cumulative meta-analysis, defined as updating a metaanalysis whenever a new eligible RCT becomes available, can be used to address this (39). However, the problem is that the median time taken for a primary study to be incorporated into a meta-analysis ranges from 2.5 to 6.5 years (40).…”
Section: Simulation Of a Living Meta-analysismentioning
confidence: 99%
“…The feasibility and sustainability of living systematic reviews can be supported by the synergic interaction of human effort and machine automation (135). A recent empirical study has demonstrated that prospectively planned living network meta-analyses produced strong evidence against the null hypothesis more often-and earlier-than conventional pairwise meta-analyses (39).…”
Section: Individual Participant Data Living Meta-analysesmentioning
confidence: 99%
“…It should be noted that both ( ) and are dependent on the characteristics being considered, the medical field and the research question and therefore the criteria for their definition are specific to every NMA. Although such an approach seems to require additional time and resources than current practices in NMA, recent directions in evidence synthesis that encourage living systematic reviews and live cumulative network meta-analyses within the context of a research community are well compatible to our method [28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%